2016
DOI: 10.1021/acs.jpcc.5b11264
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Structural Change in Pure-Silica MEL upon the Adsorption of Argon

Abstract: In this work, we investigate the structure of argon adsorbed on pure-silica MEL at liquid nitrogen temperature. Our goal is to provide a microscopic interpretation for the appearance of a substep in the adsorption isotherm at intermediate loadings before saturation. For that purpose, we first perform time-of-flight neutron diffraction experiments of the loaded zeolite, before and after the substep. The measured spectra reveal that, after the substep, a considerable ordering of the adsorbate builds up, but ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Other reasons of these discrepancies may be higher flexibility of the MEL framework or its phase transition upon adsorption. Such transitions were reported for adsorption of toluene and argon. , Therefore, the force field used for molecular simulations could not fully reflect adsorption phenomena for this particular zeolite. It is worth noticing that the level of agreement between the calculated and experimental isotherms obtained by Marguta et al is very close to that found for adsorption isobars of C6–C8 in MEL in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Other reasons of these discrepancies may be higher flexibility of the MEL framework or its phase transition upon adsorption. Such transitions were reported for adsorption of toluene and argon. , Therefore, the force field used for molecular simulations could not fully reflect adsorption phenomena for this particular zeolite. It is worth noticing that the level of agreement between the calculated and experimental isotherms obtained by Marguta et al is very close to that found for adsorption isobars of C6–C8 in MEL in this work.…”
Section: Resultsmentioning
confidence: 99%
“…To finalize, we would like to stress the usefulness of the N -RMC method to extract structural models compatible with experimentally measured diffraction patterns of adsorbed fluids on zeolites. In a previous work, we have applied this method to the adsorption of a simple gas, such as argon, on pure silica MEL . In this work, we show that the method is also applicable for more complex molecules, such as toluene.…”
Section: Summary and Conclusionmentioning
confidence: 77%
“…The N -RMC method is a variant of RMC modeling specifically designed to deal with tightly confined media. As the method has already been detailed elsewhere, , only a brief description is provided here. In short, the N -RMC method consists in performing, in addition to particle/molecule displacement and rotation attempts, insertion and deletion trials for adsorbate molecules.…”
Section: Simulationsmentioning
confidence: 99%
See 2 more Smart Citations